Common and distinct brain activity associated with risky and ambiguous decision-making. (1st April 2020) - Poudel, Ranjita; Riedel, Michael C.; Salo, Taylor; Flannery, Jessica S.; Hill-Bowen, Lauren D.; Eickhoff, Simon B.; Laird, Angela R.; Sutherland, Matthew T.
Highlights: Common and distinct brain activity linked to risky and ambiguous decisions. Common activity convergence for all decision-making (DM) domains observed in insula. Risky-DM involve activity in regions linked to reward and affective functions. Ambiguous-DM involve activity in regions linked to affectively-neutral functions. Drug users (vs. non-users) show less activity convergence in reward-related regions. Abstract: Two often-studied forms of uncertain decision-making (DM) are risky-DM (outcome probabilities known) and ambiguous-DM (outcome probabilities unknown). While DM in general is associated with activation of several brain regions, previous neuroimaging efforts suggest a dissociation between activity linked with risky and ambiguous choices. However, the common and distinct neurobiological correlates associated with risky- and ambiguous-DM, as well as their specificity when compared to perceptual-DM (as a 'control condition'), remains to be clarified. We conducted multiple meta-analyses on neuroimaging results from 151 studies to characterize common and domain-specific brain activity during risky-, ambiguous-, and perceptual-DM. When considering all DM tasks, convergent activity was observed in brain regions considered to be consituents of the canonical salience, valuation, and executive control networks. When considering subgroups of studies, risky-DM (vs. perceptual-DM) was linked with convergent activity in the striatum and anterior cingulate cortex (ACC), regions associated with reward-related processes (determined by objective functional decoding). When considering ambiguous-DM (vs. perceptual-DM), activity convergence was observed in the lateral prefrontal cortex and insula, regions implicated in affectively-neutral mental processes (e.g., cognitive control and behavioral responding; determined by functional decoding). An exploratory meta-analysis comparing brain activity between substance users and non-users during risky-DM identified reduced convergent activity among users in the striatum, cingulate, and thalamus. Taken together, these findings suggest a dissociation of brain regions linked with risky- and ambiguous-DM reflecting possible differential functionality and highlight brain alterations potentially contributing to poor decision-making in the context of substance use disorders.